Food security and household consumption patterns in Slovakia - Marian Rizov; Andrej Cupak; Jan Pokrivcak (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2014)
We investigate the food security situation of Slovak households in terms of both access to food and quality of the diet consumed by estimating food demand system and diet diversity demand models using household budget survey data over the period 2004 - 2010. In most samples demand for meat and fish and fruits and vegetables is expenditure and own-price elastic. On average all five food groups investigated are found to be normal goods. Rural and low-income households appear more expenditure and price sensitive compared to the urban and high-income ones. Results from quantile regressions indicate that income has a positive while uncertainty has a negatively effect on the diversity of the diet as the effects are stronger in more vulnerable, low income and rural consumer subsamples. Overall the food security situation in Slovakia appears to have improved over time, since the country's EU accession.
Keywords: D12; I12; O52; Q18; 330; food security; demand; QUAIDS; elasticity; diet diversity; Slovakia